Respuesta :
Answer:
y = -2x² + 3x
Step-by-step explanation:
The y-intercept of 0 tells you the constant is zero.
You can find the coefficients "a" and "b" in the form
y = ax² +bx +0
by substituting the data points that are not the y-intercept.
For x=-1, ...
-5 = a(-1)² +b(-1) = a - b
For x=2, ...
-2 = a(2)² +b(2) = 4a +2b
___
These two equations can be solved by your favorite method. Here's one way:
You can divide the second equation by 2 and add the first:
(-2)/2 +(-5) = (4a +2b)/2 +(a -b)
-6 = 3a
-2 = a
Then you can use either equation to find b.
-5 = -2 -b . . . substitute for "a" in the first equation
b = 3 . . . . . . add b+5
___
Now, you know the quadratic is
y = -2x² +3x
_____
Alternate solution
You can let your graphing calculator or spreadsheet program tell you the equation of a quadratic regression using these points. The attached shows one such result. (It is the same as above.)
![Ver imagen sqdancefan](https://us-static.z-dn.net/files/d70/b5b790bb8ffb302fbe81b0d58936fbfb.png)
Answer: y = -2x² + 3x
Step-by-step explanation:
The standard form of a quadratic equation is: y = ax² + bx + c
Input the x, y coordinates provide to create three equations. Then solve the system of equations
(0, 0) → 0 = a(0)² + b(0) + c
0 = 0 + 0 + c
0 = c
(-1, -5) and c = 0 → -5 = a(-1)² + b(-1) + 0
-5 = a + -b
(2, -2) and c = 0 → -2 = a(2)² + b(2) + 0
-2 = 4a + 2b
-5 = a - b → 2(-5 = a - b) → -10 = 2a - 2b
-2 = 4a + 2b → 1(-2 = 4a + 2b) → -2 = 4a + 2b
-12 = 6a
÷6 ÷6
-2 = a
-5 = a - b
-5 = -2 - b
-3 = -b
3 = b
a = -2, b = 3, c = 0 → y = -2x² + 3x + 0